Pediatric humoral immune responses and infection risk after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and two-dose vaccination during SARS-CoV-2 omicron BA.5 and BN.1 variants predominance in South Korea - Choi, Hyun-Woo; Achangwa, Chiara; Park, Joonhong; Lee, Sun Min; Lee, Nan Young; Jeon, Chae-Hyeon; Choi, Jeong-Hwa; Do, Hyun Kyung; Nam, Jeong-Hyun; Lee, June-Woo; Kim, Byoungguk; Ryu, Sukhyun; et al. (Frontiers in Immunology, 2023)
Background Humoral immune responses and infection risk after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and coronavirus disease 2019 (COVID-19) vaccination during the Omicron BA.5 and BN.1 variants predominant period remains unexplored in pediatric population. Methods We examined anti-spike (anti-S) immunoglobulin G (IgG) responses in a total of 986 children aged 4−18 years who visited outpatient clinics between June 2022 and January 2023, with a history of SARS-CoV-2 infection alone, completed two doses of COVID-19 vaccination alone, vaccine-breakthrough infection (i.e., infection after the single dose of vaccination), and no antigenic exposure. Furthermore, to determine SARS-CoV-2 infection risk, the incidence of newly developed SARS-CoV-2 infection was investigated up to March 2023. Results The anti-S IgG levels in the ‘vaccine-breakthrough infection’ group exceeded those in the ‘infection alone’ and ‘vaccination alone’ groups (both P <0.01). Furthermore, the ‘vaccination alone’ group experienced more rapid anti-S IgG waning than the ‘infection alone’ and ‘vaccine-breakthrough infection’ groups (both P <0.01). We could not identify newly developed SARS-CoV-2 infection in the ‘vaccine-breakthrough infection’ group. Conclusion Our findings suggest that hybrid immunity, acquired from SARS-CoV-2 infection and COVID-19 vaccination, was a potentially higher and longer-lasting humoral immune response and protected against SARS-CoV-2 infection in pediatric population during Omicron BA.5 and BN.1 variants predominant.